Pola Pendidikan Ekonomi Keluarga dalam Membentuk Rasionalitas Ekonomi dan Kewirausahaan - Dinar, Muhammad; Sukran, Putri Anggelia; Hasan, Muhammad; Supatminingsih, Tuti; Arisah, Nur (Ideas Publishing, 2024)
In general, families are less aware of the important impact of economic learning aspects on children so that they grow up as consumers who are not aware of the value of money. This study aims to determine the pattern of economic education applied by parents in forming economic rationality and entrepreneurship in children. This research used a qualitative method with a total of 6 informants whose criteria were traders. The results of the research are that the family economic education patterns applied by business actors are democratic, authoritarian, permissive and situational. However, the democratic education pattern is the economic education pattern in the family that is most often used in forming economic rationality and entrepreneurship in children.